Pengaruh Harga dan Kualitas Makanan Terhadap Minat Beli Aplikasi Online Pada Tempat Makan Bebek Bakar Ayayo Bandung - Enggriani, Mimi; Nabila, Azka (Jurnal Ilmiah Pariwisata; Vol 27 No 2 (2022): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v27i2.1617, 2022)
This study aims to determine the effect of price and quality of food on buying interest at the 'Bebek Bakar Ayayo' restaurant in Bandung. This type of research is descriptive research with a quantitative approach. The research method used is multiple regression analysis. The sample used is 100 respondents with accidental sampling method. The results showed that the price and quality of food had a significant effect on buying interest either partially or simultaneously. The price of the Duck Bakar Ayayo food menu has an affordable price followed by good product quality. The place to eat Bebek Bakar Ayayo always improves bright colors, good food appearance, standard portions, attractive food shapes, texture and softness, good aroma, sufficient maturity level, delicious and delicious taste. Suggestions in this study, the place to eat Duck Bakar Ayayo needs to carry out the right policy related to price, namely applying a menu price that is more adequate than other similar places to eat roasted duck, the price of the food menu that is set should be more adequate than other similar places to eat roast duck. ; The quality of food that will be served to consumers must remain consistent so that the taste of the food does not change so that consumers remain satisfied and interested in buying. Keywords: Price, Food Quality, Buying Interest